Impact of Knee Scooter Flexion Position on Venous Flow Rate. (January 2019) - Ciufo, David J.; Anderson, Michael R.; Baumhauer, Judith F.
Background: The knee scooter is a commonly used mobility device in the setting of unilateral below-knee immobilization. The bent-knee posture has been shown to decrease venous flow in a seated position, but the knee scooter differs as the patient is weightbearing through the affected extremity. Our goal was to investigate the effects of knee scooter positioning on popliteal venous flow. Methods: Duplex ultrasonography was performed to obtain venous diameter and flow velocity of the popliteal vein on healthy subjects over the age of 18 without immobilization. Measurements were performed on the left knee of each subject while standing and with the same knee flexed on the knee scooter, by 2 physicians trained in ultrasound techniques. Mean velocity, peak velocity, vessel diameter, and volumetric flow rate were calculated and t tests were performed for each variable. A power analysis was performed, determining that 9 subjects would provide 80% power with an alpha of 0.05. A total of 13 subjects participated in the study. Mean age was 33 (range 20-56) years, with 6 females and 7 males. Results: Measurements of subjects while standing and on the knee scooter demonstrated a significant decrease in mean velocity (6.5 vs 3.2 cm/s, P < .01) and volumetric flow rate (227.8 vs 106.2 mL/min, P < .01) while subjects were using the scooter. Vessel diameter (0.82 vs 0.78 cm, P = .15) and peak velocities (19.8 vs 14.7 cm/s, P = .19) were not significantly different between standing and kneeling positions. Conclusion: Our findings demonstrated a statistically significant decrease in volumetric flow rate in subjects using a knee scooter device with a flexed knee. Although venous stasis is a known risk factor for DVT, flow rate thresholds for increased thrombus formation are not well defined. The duration of scooter use, or flexed knee positioning, may have some effect on the degree of stasis. This finding should caution orthopedists to consider the risk attributed to the knee scooter as part of their overall patient assessment. Level of Evidence: Level II, therapeutic, comparative study.